Isolation and characterization of proteins that interact with a pollen-specific calmodulin-binding protein - Shin, Sung-Bong, author; Reddy, A. S. N., advisor (Colorado State University. Libraries, 2008)
Calcium and calmodulin, a calcium sensor, are implicated in pollen germination and tube growth. However, the mechanisms by which calcium and calmodulin regulate these processes are largely unknown. Calcium bound calmodulin regulates diverse cellular processes by modulating the activity of other proteins called calmodulin-binding proteins. Maize pollen-specific calmodulin-binding protein (MPCBP) and its homolog (NPG1, no pollen germination) from Arabidopsis were isolated previously. Studies with a knockout mutant have shown that AtNPG1 is not necessary for pollen development but is essential for pollen germination. Analysis of the Arabidopsis genome sequence with AtNPG1 revealed the presence of two other proteins (AtNPGR1, NPG-Related1; AtNPGR2, NPG-Related 2) that are closely related to AtNPG1. To gain insights into the function of AtNPG1 and AtNPGRs, I focused my research on characterization of these proteins. Specifically, my research focused on in vivo localization of AtNPG1 in pollen grain and tube, interaction between AtNPGs, isolation and characterization of AtNPG1 interacting proteins, and functional analysis of AtNPGR1 in plant development. Transgenic plants containing GFP fused to AtNPG1 promoter showed GFP expression only in mature and germinating pollen, suggesting that the promoter is active only in pollen. Localization of GFP-AtNPG1, driven by AtNPG1 promoter, during different stages of pollen germination revealed uniform cytosolic distribution of GFP-AtNPG1 in the growing pollen tube that was similar to GFP alone. However, the observed uniform localization of GFP-AtNPG1 is not due to degraded fusion protein. AtNPGRs, like AtNPG1, bind calmodulin in a calcium-dependent manner. The calmodulin-binding domain in AtNPGs was mapped to a short region. AtNPG1 and AtNPGRs have several tetratricopeptide repeats (TPRs) that are known to be involved in protein-protein interaction. I tested the interaction among AtNPGs using the yeast two-hybrid analysis. AtNPG1-BD interacted with itself-AD and AtNPGR1-AD and AtNPGR2-AD. AtNPGR1-BD interacted with itself-AD, AtNPG1-AD and AtNPGR2-AD. However, AtNPGR2-BD did not interact with AtNPG1-AD or AtNPGR1-AD and showed a very weak interaction with itself-AD. To study the role of AtNPG1, AtNPG1 interacting proteins from a petunia pollen library were isolated in a yeast two-hybrid screen and identified as pectate lyase-like proteins. Using in vivo and in vitro protein-protein interaction assays, I show that AtNPGs interacts with four Arabidopsis pectate lyase-like (PLL) proteins with the highest similarity to petunia PLLs. Truncated AtNPG1 lacking the TPR 1 did not interact with most of partners or showed drastically decreased interaction with some proteins, suggesting that the TPR 1 domain is essential for this interaction. To understand the role of Arabidopsis PLL proteins, we characterized these using molecular and biochemical tools. Of the 26 Arabidopsis PLLs, fourteen were expressed in pollen and four AtPLLs were highly expressed. These four AtPLLs showed expression in other tissues also. Analysis of pectate lyase activity in Arabidopsis tissues (flower, root, stem, and leaf) revealed enzyme activity in all four tissues and the activity varied depending on the buffer pH. To see if AtNPG1 interacting AtPLLs have enzyme activity, four AtPLLs were expressed in bacteria or yeast and assayed for their enzyme activity under different conditions with different substrates. None of the AtPLLs expressed by bacterial or yeast showed pectate lyase activity. To discover the role of AtPLL in Arabidopsis development, one AtPLL mutant, atpll8, was isolated. Phenotypic analysis of atpll8 under different growth condition showed no significant differences as compared to wild type. AtNPGR1, unlike AtNPG1, is expressed in tissues other than pollen. To understand the role of AtNPGR1 in plant development, I isolated an atnpgr1 knockout mutant and characterized its phenotype under different growth conditions. The atnpgr1 showed a sugar resistance phenotype, suggesting that it might be involved in sugar sensing and/or signaling pathway. Expression of hexokinase (Hxk), an important component in sugar signaling in plants, and other genes in the Hxk pathway, revealed that NPGR1 might be involved in an Hxk independent pathway.
Keywords: calcium signaling; calmodulin; hexokinase; NPGs; plant reproduction; pollen; molecular biology; cellular biology; plant sciences